2021
DOI: 10.51821/84.4.012
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of prognostic factors in stomach cancer with helicobacter pylori: a retrospective study

Abstract: Background and study aims: The prognostic value of H. pylori, which infects more than half of the human population living in the world and plays a role in gastric cancer pathogenesis, is controversial. Our aim is to investigate the relationship between H. pylori and prognostic factors in gastric cancer. Patients and methods: The data of 110 patients (38 females and 72 males) that underwent surgeries due to gastric cancer between 2014 and 2017 were retrospectively analyzed. The relationships between survival (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…At present, Helicobacter pylori ( H. pylori ) has been identified as a carcinogen of gastric cancer [ 34 ]. Remarkably, one out of every two people is infected with Helicobacter pylori worldwide [ 35 ]. Similarly, cancers caused by Helicobacter pylori infection have a higher incidence compared to other various cancers [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, Helicobacter pylori ( H. pylori ) has been identified as a carcinogen of gastric cancer [ 34 ]. Remarkably, one out of every two people is infected with Helicobacter pylori worldwide [ 35 ]. Similarly, cancers caused by Helicobacter pylori infection have a higher incidence compared to other various cancers [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 Chronic infection is potentially related to clinical or subclinical persistent inflammation associated with tumor necrosis factor α, transforming growth factor β (TGFβ), interleukin (IL) 6, and IL-10, which are reported to be involved in both initiation and progression of malignancies. 10 Previous studies have found that persistent inflammation is closely associated with the development of some malignancies, including chronic gastritis due to Helicobacter pylori infection, a cause of gastric cancer 11 ; ulcerative colitis, a cause of colorectal cancer 12,13 ; irritation due to frequent exposure to alcohol and/or tobacco, a cause of esophageal cancer 14,15 ; and hidradenitis suppurativa, a cause of cutaneous squamous cell carcinoma. 16 On the other hand, the sole of the foot is a predilection site of melanoma unlike other cutaneous malignancies such as squamous cell carcinoma and basal cell carcinoma.…”
mentioning
confidence: 99%